« Est-ce que ça marche ? » À propos du tasfih, rituel protecteur de la virginité des jeunes filles tunisiennes - Ibtissem Ben Dridi (L’Année du Maghreb)
Through the execution of ritual acts accompanied by certain magical words, tasfih is said to protect young Tunisian girls from sexual contact and thereby guarantees their premarital virginity. A field survey conducted in 2001 revealed a rather facetious ritual, which would undoubtedly preserve virtue but at the same time allowed certain liberties. The ethnographic material collected and presented to a very diverse Tunisian audience, including the medical community, the media, politicians and bloggers, sparked unexpected reactions that focused on one nagging question: “Does it work?” Through reflection on these reactions and on the initial field survey we were able to examine sexual behavior, the vocabulary used to describe it and their heuristic significance in the analysis and understanding of the contradictions of contemporary Tunisia.